Catalytic hydrogasification characteristic of coal with diverse properties in a pressurized fluidized bed. (15th July 2021) - Yan, Shuai; Qu, Xuan; Xia, Zihong; Chen, Caixia; Bi, Jicheng
Graphical abstract: Highlights: Fluidized bed hydrogasification of coals with diverse properties. Carbon structure and sulfur content in coal affect reactivity significantly. Blending low rank coal minimized caking propensity and promoted hydrogasification. CaO migrated adjacent to Co to retard poisoning and promote catalytic activity. Effect of coal properties on hydrogasification mechanism revealed. Abstract: Coal catalytic hydrogasification is an efficient approach to produce CH4 . This study investigated hydrogasification characteristic of coal with diverse properties (caking propensity, high rank and sulfur content) in a pressurized fluidized bed. The approaches to realize high CH4 yield and stable fluidization were explored. Experimental results showed that carbon structure and sulfur content in coal were the key factors influencing hydrogasification reactivity. The mechanically mixed CaO/CaCO3 migrated into the interior of coal particle to enhance the activity of Co towards graphite carbon, and capture sulfur adsorbing on Co surface. The caking propensity of coal brought little resistance to the activity of catalyst, whereas, caused serious agglomerating phenomenon. The blending of caking coal with non-caking, low rank coals induced the active hydrogen spill-over and the volatiles-catalyst-coal interactions, which not only in-situ minimized the agglomeration propensity, but also enhanced the overall hydrogasification reactivity. Furthermore, the mechanism of hydrogasification was proposed by taking account of coal property, to broadening the application range of hydrogasification and producing CH4 efficiently (~80.0 wt% in 1.0 h).